Confinement and IR Induced Optical Nonlinearity and Enhanced Second-Order Susceptibility in Nano-Sized Crystals - Miah, Mohammad Idrish (Indonesian Journal of Material Research, 2025)
Cadmium iodide bulk- and nano-crystals are grown and doping defect and quantum-confinement effects in IR-induced optical susceptibility in the nanocrystals are investigated. Bulk-sized and intrinsic crystals are also investigated as of reference. The nanomaterials with various crystal sizes are pumped with an IR laser beam. This pump-probe experiment probes the doubledfrequency IR-induced second harmonic optical beam. The expression for the second harmonic intensity is obtained from the electric polarization of the nanomaterial process subjected to high intensity illumination. The second–order susceptibility is calculated from the experimentally measured data. The results show that a significant enhancement in the optical susceptibility is achieved in nanomaterials with moderately doping. The maximum second–order optical susceptibility is found to 0.65 pm/V. However, bulk and intrinsic crystals show no considerable second harmonic effect. A nonlinear transmittance measurement for the determination of the second-order contribution in absorption supports the effect.